2004
DOI: 10.1021/jf049180c
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactoglobulin−Dextran Conjugates:  Effect of Polysaccharide Size on Emulsion Stability

Abstract: A series of dextrans and beta-lactoglobulin were covalently conjugated and screened for their ability to stabilize oil-in-water emulsions. Dextrans with the molecular mass of 19.6 kDa, 87 kDa, 150 kDa, 500 kDa, and 2000 kDa were attached to beta-lactoglobulin via the Maillard reaction. The conjugates were then purified and evaluated as emulsifiers under neutral conditions. The ability to stabilize emulsions was determined by monitoring oil droplet size over time. Adsorption of the conjugates to the droplet sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 35 publications
2
55
2
Order By: Relevance
“…To improve functional properties of proteins including their emulsifying ability, chemical modifications have often been made. Over the past few years, there has been growing interest in the modification of proteins with sugars through the Maillard reaction [4][5][6][7][8][9][10][11][12][13][14] ; a complex network of non-enzymatic reactions between reducing sugars and protein amino groups (see ). At an early stage of the Maillard reaction, amino groups in proteins react with carbonyl groups of sugars to give 1-amino-1-deoxy-ketose, known as the Amadori compound 15) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve functional properties of proteins including their emulsifying ability, chemical modifications have often been made. Over the past few years, there has been growing interest in the modification of proteins with sugars through the Maillard reaction [4][5][6][7][8][9][10][11][12][13][14] ; a complex network of non-enzymatic reactions between reducing sugars and protein amino groups (see ). At an early stage of the Maillard reaction, amino groups in proteins react with carbonyl groups of sugars to give 1-amino-1-deoxy-ketose, known as the Amadori compound 15) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that products of the Maillard reaction exhibit improved emulsifying and foaming ability in some cases. To enhance the efficiency of globular proteins as an emulsifier, polysaccharides have often been used to covalently connect with proteins by the Maillard reaction 4,[11][12][13][14] . When the protein-polysaccharide conjugates adsorb at the oil-water interface in emulsion, polysaccharide chains will protrude into the aqueous bulk and provide a protecting layer that prevents the coalescence and flocculation of oil droplets.…”
Section: Introductionmentioning
confidence: 99%
“…According to Oliver et al (Oliver, et al, 2006), Maillard reaction is a spontaneous and naturally occurring reaction between available amino groups from a protein with reducing sugar entities from polysaccharides, which involves the Amadori rearrangement (Dunlap & Côté, 2005;. Thus, during the Maillard reaction amino groups of the protein will be consumed and as a consequence the availability of the amino groups decreases.…”
Section: Tnbs Analysismentioning
confidence: 99%
“…Because of their stable properties, this kind of bonding has been intentionally used to produce conjugated emulsifiers (Akhtar & Dickinson, 2003;Benichou et al, 2007;Dunlap & Côté, 2005;Neirynck et al, 2004;Shepherd et al, 2000;Song et al, 2002). In most of these studies, the covalent conjugation between proteins and polysaccharides has been achieved through the Maillard reaction.…”
Section: Covalent Bondsmentioning
confidence: 99%
“…Sunflower oil (20.0-wt%) Covalent conjugation providing better emulsion stability (Dunlap & Côté, 2005) 25. Lysozymes + Chitosan Corn oil (25.0-vol%) Covalent conjugate: Emulsion stability-High-molecular-type chitosan > Low molecular type (Song et al, 2002) being adsorbed to the surface of the oil droplet and the properties of a hydrophilic polysaccharide being highly hydrated by the aqueous phase.…”
Section: Lysozymes + Galactomannanmentioning
confidence: 99%